The DRD4 Exon III VNTR, Bupropion, and Associations With Prospective Abstinence - Bergen, Andrew W. (Oxford University Press, 2013)
INTRODUCTION: DRD4 Exon III Variable Number of Tandem Repeat (VNTR) variation was found to interact with bupropion to influence prospective smoking abstinence, in a recently published longitudinal analyses of N = 331 individuals from a randomized double-blind placebo-controlled trial of bupropion and intensive cognitive–behavioral mood management therapy. METHODS: We used univariate, multivariate, and longitudinal logistic regression to evaluate gene, treatment, time, and interaction effects on point prevalence and continuous abstinence at end of treatment, 6 months, and 12 months, respectively, in N = 416 European ancestry participants in a double-blind pharmacogenetic efficacy trial randomizing participants to active or placebo bupropion. Participants received 10 weeks of pharmacotherapy and 7 sessions of behavioral therapy, with a target quit date 2 weeks after initiating both therapies. VNTR genotypes were coded with the long allele dominant resulting in 4 analysis categories. Covariates included demographics, dependence measures, depressive symptoms, and genetic ancestry. We also performed genotype-stratified secondary analyses. RESULTS: We observed significant effects of time in longitudinal analyses of both abstinence outcomes, of treatment in individuals with VNTR long allele genotypes for both abstinence outcomes, and of covariates in some analyses. We observed non-significantly larger differences in active versus placebo effect sizes in individuals with VNTR long allele genotypes than in individuals without the VNTR long allele, in the directions previously reported. CONCLUSIONS: VNTR by treatment interaction differences between these and previous analyses may be attributable to insufficient size of the replication sample. Analyses of multiple randomized clinical trials will enable identification and validation of factors mediating treatment response.